4+7x-3=9x+13-6x

Simple and best practice solution for 4+7x-3=9x+13-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+7x-3=9x+13-6x equation:


Simplifying
4 + 7x + -3 = 9x + 13 + -6x

Reorder the terms:
4 + -3 + 7x = 9x + 13 + -6x

Combine like terms: 4 + -3 = 1
1 + 7x = 9x + 13 + -6x

Reorder the terms:
1 + 7x = 13 + 9x + -6x

Combine like terms: 9x + -6x = 3x
1 + 7x = 13 + 3x

Solving
1 + 7x = 13 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
1 + 7x + -3x = 13 + 3x + -3x

Combine like terms: 7x + -3x = 4x
1 + 4x = 13 + 3x + -3x

Combine like terms: 3x + -3x = 0
1 + 4x = 13 + 0
1 + 4x = 13

Add '-1' to each side of the equation.
1 + -1 + 4x = 13 + -1

Combine like terms: 1 + -1 = 0
0 + 4x = 13 + -1
4x = 13 + -1

Combine like terms: 13 + -1 = 12
4x = 12

Divide each side by '4'.
x = 3

Simplifying
x = 3

See similar equations:

| 6j+-2j+14j-7j+-9n-(-19)=-15 | | m(a+5)=Kfora | | -0.1x^2-x+31=0.1x^2+2x+11 | | 6j+-2j+14j-7j+-9-(-19)=-15 | | 0.2x^2+x-20=0 | | 6j+-2j+14j-7j+(-19)=-15 | | 6j+2j+14j-7j+(-19)=-15 | | r-r+5r-2r=9 | | -5c+14c+-7=11 | | 5b-19b-(-20b)-(-14)=-10 | | 32+0.90m=2(31+0.30m) | | 20m-10m+2m-8m+2m=6 | | 5u+4u-6u-u=12 | | n^2-n-480=0 | | log(base)2(x^2-3x-66)=2 | | 20n-12n+-9n=8 | | 2x=17+2 | | -3h+-h+6h+-7h=15 | | 5x+26=10x-10 | | -3h+-h+6h+7h=15 | | 8x-4+4x+28=5x+10 | | 2y=3+6y | | 14p+3p-17p+p+p=20 | | 900n-360=0 | | 8x-4=5x+10 | | 8x-4+5x+10=4x+28 | | 5(x+3)+8=-2(x-8) | | 3r+-16r+9r=4 | | 8x-4=5x+10+4x+28 | | 3r+16r+9r=4 | | -4j+10=-8j-10 | | 6+2x-5=8x+37-2x |

Equations solver categories